1986
DOI: 10.1172/jci112503
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar epithelial damage. A critical difference between high pressure and oleic acid-induced low pressure pulmonary edema.

Abstract: The present study was designed to compare high pressure pulmonary edema (HPPE) and oleic acid-induced low pressure pulmonary edema (OAPE) in dogs when similar amounts of extra vascular water were present in the lung. The high pressure edema was produced by intravenous fluid overload and by inflating an aortic balloon catheter (n = 6). The low pressure edema was produced by the injecting 0.08 mg/kg oleic acid suspended in 5 ml saline (n = 6). Comparison of the difference between initial control measurements and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 24 publications
4
24
0
3
Order By: Relevance
“…4). Alveolar flooding may occur earlier because oleic acid has been shown recently to cause both an endothelial and epithelial injury (13). With an intact epithelial barrier, edema may accumulate in the interstitium, raising pressure, and effusions might occur more rapidly (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Alveolar flooding may occur earlier because oleic acid has been shown recently to cause both an endothelial and epithelial injury (13). With an intact epithelial barrier, edema may accumulate in the interstitium, raising pressure, and effusions might occur more rapidly (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar flooding may occur earlier because oleic acid has been shown recently to cause both an endothelial and epithelial injury (13). With an intact epithelial barrier, edema may accumulate in the interstitium, raising pressure, and effusions might occur more rapidly (13,14). In separate experiments, we have studied the time course of pleural effusion formation in volume-overload pulmonary edema in sheep and found that the effusions do begin to accumulate within the first 1 h after the development of interstitial edema (15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subtle but functionally important alterations would go undetected at the light microscopic level, e.g. only by electron microscopy is it possible to distinguish permeability oedema due to primary blood-air barrier injury in ALI from the lesions in hydrostatic oedema [36][37][38][39] and to analyse intra-alveolar surfactant subtype alterations [40][41][42][43]. Primary chemical fixation ''from behind'' by controlled vascular perfusion with a glutaraldehyde-containing fixative followed by a phospholipid-stabilising protocol is the method of choice when subsequent stereological analysis of oedema and surfactant has to be performed [44][45][46][47][48][49].…”
Section: Stereological Assessment Of Alimentioning
confidence: 99%
“…The alteration of fluid balance in the lung that results in pulmonary edema can be caused by increased hydrostatic pressure or increased permeability of the pulmonary capillary bed (Guyton and Lindsey, 1959;Gorin and Stewart, 1979;Montaner et al, 1986;Matthay et al, 2002). High-permeability pulmonary edema results from an increase in the vascular permeability of the lung, causing an accumulation of fluid and protein in the lung interstitium and air spaces (Gorin and Stewart, 1979;Montaner et al, 1986;Matthay et al, 2002). The increase in permeability can be initiated by a variety of factors, and is directly related to reversible physical modifications of the pulmonary endothelium (Fraser et al, 1999;Matthay and Martin, 2005;Leaver and Evans, 2007;Wheeler and Bernard, 2007).…”
Section: Introductionmentioning
confidence: 99%